Differential Harnack Estimate for A Nonlinear Parabolic Equation under List's Flow - Ma, Bingqing (Communications in Mathematics and Applications, 2013)
In this paper, we prove a differential Harnack inequality for positive solutions of nonlinear parabolic equations of the type \[f_t=\Delta f-f\log f+Sf,\] see (1.9). Here the metric is evolving under the List's flow.